Television watching and risk of colorectal adenoma - Cao, Y (Br J Cancer, 2015)
BACKGROUND: Prolonged TV watching, a major sedentary behaviour, is associated with increased risk of obesity and diabetes and may involve in colorectal carcinogenesis. METHODS: We conducted a cross-sectional analysis among 31 065 men with ⩾1 endoscopy in the Health Professionals Follow-up Study (1988–2008) to evaluate sitting while watching TV and its joint influence with leisure-time physical activity on risk of colorectal adenoma. Logistic regression was used to calculate odds ratios (ORs) and 95% confidence intervals (CIs). RESULTS: Prolonged sitting while watching TV was significantly associated with increased risk of colorectal adenoma (n=4280), and adjusting for physical activity or a potential mediator body mass index did not change the estimates. The ORs (95% CIs) across categories of TV watching (0–6, 7–13, 14–20, and 21+ h per week) were 1.00 (referent), 1.09 (1.01–1.17), 1.16 (1.06–1.27), and 1.10 (0.97–1.25) (OR per 14-h per week increment=1.11; 95% CI: 1.04–1.18; P(trend)=0.001). Compared with the least sedentary (0–6 h per week of TV) and most physically active (highest quintile) men, the most sedentary (14+ h per week) and least active (lowest quintile) men had a significant increased risk of adenoma (OR=1.25; 95% CI: 1.05–1.49), particularly for high-risk adenoma. CONCLUSIONS: Prolonged TV viewing is associated with modest increased risk of colorectal adenoma independent of leisure-time physical activity and minimally mediated by obesity.